2018
DOI: 10.1177/0261018318766509
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion, neoliberalism and resistance: The role of social workers in implementing social policies in Chile

Abstract: The views of social workers in Chile are rarely heard and considered in the policy debates. This article addresses this lacuna by examining discourses of social exclusion and underlying assumptions held by social workers with responsibility for implementing social policy interventions in Chile. It draws upon the findings of a study involving interviews with senior social workers from two large non-governmental organisations (NGOs) tackling social exclusion. We found that individual-based narratives and neolibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Findings based on self-report questionnaires examining a social protest movement in Israel 2011 found that adolescents with stronger feelings of meaning and coherence, whose value systems supported enhancing civic engagement and efficacy, were more hopeful and healthier [ 42 ]. In the context of oppression and sociopolitical development, civic engagement may provide a self-liberating mechanism from social oppression and can lead to the development of a critical awareness of societal dynamics, power relationships, and social justice [ 43 , 44 , 45 ]. This suggests that positive emotions and the enjoyment associated with social activity can relieve an often draining, exhausting, alienating, and muted reality [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings based on self-report questionnaires examining a social protest movement in Israel 2011 found that adolescents with stronger feelings of meaning and coherence, whose value systems supported enhancing civic engagement and efficacy, were more hopeful and healthier [ 42 ]. In the context of oppression and sociopolitical development, civic engagement may provide a self-liberating mechanism from social oppression and can lead to the development of a critical awareness of societal dynamics, power relationships, and social justice [ 43 , 44 , 45 ]. This suggests that positive emotions and the enjoyment associated with social activity can relieve an often draining, exhausting, alienating, and muted reality [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the extreme neoliberal economic framework of Chile has, for years, conceived education, health and water as consumption goods, limiting structurally the access to basic and fundamental needs (Harvey, 2007). Thus, economic poverty represents the cornerstone of the process of social exclusion (i.e., social disadvantage) in Chile (Muñoz-Arce & Pantazis, 2018).…”
Section: Socio-economic Trends and Environmental Regulationsmentioning
confidence: 99%
“…Meningkatnya kemampuan anggota Kube dalam mengatasi masalah-masalah yang mungkin terjadi dalam keluarganya maupun dengan lingkungan sosialnya. Pelatihan professional telah mempengaruhi kehidupan berdemokrasi dan perlawanan kolektif dalam menyelesaikan berbagai masalah (Muñoz Arce & Pantazis, 2019). Intervensi pelatihan keterampilan dapat memecahkan masalah terutama membantu mengurangi penyimpangan (Seyyedi Nasooh Abad et al, 2021).…”
Section: Implementasi Kegiatan Pengabdianunclassified